Divided majority and information aggregation: Theory and experiment - Laurent Bouton; Micael Castanheira; Aniol Llorente-Saguer (Max Planck Institute for Research on Collective Goods, 2012)
This paper both theoretically and experimentally studies the properties of plurality and approval voting when the majority is divided as a result of information imperfections. The minority backs a third alternative, which the majority views as strictly inferior. The majority thus faces two problems: aggregating information and coordinating to defeat the minority candidate. Two types of equilibria coexist under plurality: either voters aggregate information, but this requires splitting their votes, or they coordinate but cannot aggregate information. With approval voting, expected welfare is strictly higher, because some voters multiple vote to achieve both goals at once. In the laboratory, we observe both types of equilibrium under plurality. Which one is selected depends on the size of the minority. Approval voting vastly outperforms plurality. Finally, subject behavior suggests the need to study asymmetric equilibria.
Keywords: C92; C72; D70; P16; 330; experiments; multicandidate elections; plurality; approval voting; Abstimmungsregel; Informationsverhalten; Wahlverhalten; Test